DEVELOPMENT OF POP-UP BOOK LEARNING MEDIA IN SCIENCE SUBJECT AT ELEMENTARY SCHOOL - Lili Kasmini; Akmaluddin; Indrawati Berutu (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
One of the many obstacles faced by elementary teachers in learning is that lack of suitable teaching media and material thus failed to attract students’ attention during the teaching-learning process, especially in science learning in which abstract concepts usually require concrete objects to enhance students’ understanding. The purpose of this research is to determine the students’ learning outcomes by using pop-up books as a media in teaching science for the elementary students. By using the saturation sampling technique, a total of 16 fourth-grade students in Aceh Singkil involve in this study. This Research and Development (R&D) study adopts the ADDIE instructional systems design framework model to develop the product. The results shows that the designed pop-up book is very valid thus can be used as the material for science teaching. Furthermore, the media can increase students’ knowledge and can help student understand the concept easily